Bioengineering Human Neurological Constructs Using Decellularized Meningeal Scaffolds for Application in Spinal Cord Injury - Vishwakarma, Sandeep Kumar; Bardia, Avinash; Lakkireddy, Chandrakala; Paspala, Syed Ameer Basha; Khan, Aleem Ahmed (Frontiers in Bioengineering and Biotechnology, 2018)
Spinal cord injury (SCI) is one of the most devastating conditions echoes with inflammation, enhanced fibrosis and larger axonal gaps due to destruction of neurological cells which has caused continuous increasing mortality rate of SCI patients due to absence of suitable treatment modalities. The restoration of structural and functional aspect of damaged neurological tissues at the lesion site in spinal cord has been challenging. Recent developments have showed tremendous potential of neural stem cell-based strategies to form a neuronal relay circuit across the injury gap which facilitates some levels of improvement in SCI condition. However, to provide better therapeutic responses, critical mass of grafted cells must survive for long-term and differentiate into neuronal cells with well developed axonal networks. Hence, development of tissue specific biological neuronal constructs is highly desirable to provide mechanical and biological support for long-term survival and function of neurological cells within natural biological niche. In this study, we report development of a tissue specific neuronal constructs by culturing human neural precursor cells on decellularized meningeal scaffolds to provide suitable biological neuronal construct which can be used to support mechanical, structural and functional aspect of damaged spinal cord tissues. This particular tissue specific biological construct is immunologically tolerable and provides precisely orchestral three-dimensional platform to choreograph the long-distance axonal guidance and more organized neuronal cell growth. It passes sufficient mechanical and biological support enriched with several crucial neurotrophins required for long-term survival and function of neurological cells which is required to form proper axonal bridge to regenerate the damaged axonal connectomes at lesion-site.